Effect of multimedia pedagogy on students’ achievement in hybridization and molecular shapes in selected secondary schools in volta region - Bindor, Alexander Bonye; Mpuangnan, Kofi N; Boniface; Ametepey, Israel (Edelweiss Applied Science and Technology, 2026)
This study examined the effect of multimedia pedagogy on students’ academic achievement in hybridization and molecular shapes among selected secondary schools in the Volta Region. The study focused on four cognitive levels of Bloom’s Taxonomy: remembering, understanding, applying, and analyzing. A quasi-experimental pretest–posttest control group design was employed, involving 81 SHS 2 chemistry students drawn from two existing classroom cohorts. The experimental group (44 students) received instruction through multimedia pedagogy, while the control group (37 students) was taught using conventional teaching methods over a four-week period. Data were collected using the Hybridization and Molecular Shapes Performance Test and analyzed using descriptive statistics and one-way ANOVA. The findings revealed a significant improvement in the experimental group’s academic performance, with mean scores increasing from 45.20 in the pre-test to 72.35 in the post-test. The results further indicated statistically significant differences across cognitive levels, with students demonstrating stronger performance at the application level than at the comprehension and analysis levels. It was recommended that curriculum frameworks should integrate interactive digital resources to complement and enhance traditional teaching methods. Implications includes chemistry teachers should integrate multimedia-based instructional approaches into classroom practice to improve learners’ understanding of abstract concepts and enhance overall academic achievement.